ANALISIS MODEL PROBLEM BASED LEARNING TERHADAP MINAT BELAJAR SISWA PADA TEMA EKOSISTEM DI KELAS IV SD NURSYAMSIANI - Dwi Lestari; Arrini Shabrina Anshor (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The objectives to be achieved in this research are: to find out whether problem based learning can help teachers in the teaching and learning process, to find out whether the problem based learning model can increase students' interest in learning. The subject of this research is Nursyamsiani Elementary School. The object of this research is the Problem Based Learning Model. This research was conducted to find out the reasons why students are bored studying in class, namely: conducting observations, conducting interviews, giving questionnaires and questionnaires. From the results of the research and analysis carried out, it can be concluded that: the problem based learning model can help teachers in the teaching and learning process. students are interested in learning using problem based learning. Children like learning with a problem based learning model